A bibliometric analysis of the application of imaging in sleep in neurodegenerative disease - Li, Mengfei; Jiang, Zhenzhen; Wen, Ru; Liu, Chen; Wang, Jian (Frontiers in Aging Neuroscience, 2023)
Objective The purpose of this study was to examine the current state of the application of imaging in sleep research in degenerative disease, as well as hotspots and trends. Materials and methods A search was conducted on the Web of Science Core Collection (WoSCC) between 1 September 2012, and 31 August 2022 for literature related to sleep imaging. This study analyzed 7,679 articles published in this field over the past 10 years, using CiteSpace to analyze tendencies, countries, institutions, authors, and hotspots. Results There were 7,679 articles on the application of imaging to sleep research published by 566 institutions located in 135 countries in 1,428 journals; the number of articles was increasing on a yearly basis. According to keyword analysis, the research direction of the application of imaging in sleep research focused on the effects of degenerative diseases on sleep, such as Parkinson’s disease, Alzheimer’s disease, and small vessel disease. A literature evaluation found that Parkinson’s disease, insomnia, sleep quality, and rapid eye movement sleep behavior disorder were the top research trends in this field. Conclusion A growing body of research has focused on sleep disorders caused by degenerative diseases. In the application of imaging to sleep research, magnetic resonance functional brain imaging represents a reliable research method. In the future, more aging-related diseases may be the subject of sleep-related research, and imaging could provide convenient and reliable evidence in this respect.